DISTINCTIVE FEATURES IN THE ORGANIZATION OF INDEPENDENT WORK IN THE MUSICAL ACTIVITIES OF STUDENTS (Academia Science Repository, 2023)
The article describes the problems in learning musical works independently, the lack of skills and competencies in learning musical works independently as a result of low level of use of educational literature and internet resources in information resource centers, lack of skills in playing instruments, vocals, singing in a choir, insufficient musical literacy.